Informational Interdependencies: System Structure Induced by Accounting Information. - Prakash, Prem; Rappaport, Alfred (The Accounting Review, 1975)
Abstract The article develops a frame of reference which emphasizes the fact that a firm, in functioning as a system within the parameters determined by its environment, itself functions as an element in a higher level system, namely, the economy, wherein it interacts and interrelates with other elements and so takes part in the process of determining the very parameters within which it must function internally. The first section of the article briefly presents the informational viewpoint and lays the groundwork for looking at the firm and its embedding in the economy from this viewpoint. The second section describes some of the salient informational interdependencies both internal to the firm and between the firm and its environment, highlighting thereby the role of accounting information as seen from the proposed frame of reference. Information plays an essential role in the functioning of purposeful, decision-making elements and flows of information among such elements are basic to all social systems.